PENGARUH SUASANA TOKO DAN KENYAMANAN LOKASI TERHADAP NIAT PEMBELIAN ULANG YANG DIMEDIASI OLEH KEPUASAN PELANGGAN PADA PELANGGAN RUMAH MAKAN CUT BIT ACEH BESAR - Muhammad Al Attariq; Muhammad Ridha Siregar (Jurnal Ilmiah Mahasiswa Ekonomi Manajemen, 2022)
This study aims to measure the effect of Store Atmosphere and LocationConvenience towards Repurchase Intention mediated by Customer Satisfaction oncutbitrestaurantcustomers.Amounting200respondents.Datacollectionequipment that used in this research is a questionnaire. The sampling techniquethatusedispurposivesampling.StructuralEquationModelling(SEM)wasusedasan analytical method to determine the effect between the variable involved. BasedontheresultsoftheSEManalysisidentifiedthatStoreAtmospherehasasignificanteffect on Repurchase Intention, Location Convenience has a significant effect onRepurchase Intention,Store Atmopshere has a significanteffectonCustomerSatisfaction,LocationConveniencehasasignificanteffectonCustomerSatisfaction,CustomerSatisfactionhasasignificanteffectonRepurchaseIntention,CustomerSatisfactionmediatestheeffectofStoreAtmosphereonRepurchaseIntention,CustomerSatisfactionmediatestheeffectofLocationConvenience onRepurchaseIntention.